2013
DOI: 10.1111/jace.12220
|View full text |Cite
|
Sign up to set email alerts
|

In situ Diamond Anvil Cell–Raman Spectroscopy and Nanoindentation Study of the Pressure‐Induced Phase Transformation in Pure and Zinc‐Doped β‐Eucryptite

Abstract: b-eucryptite (LiAlSiO 4 ), a member of the family of lithium aluminum silicates, is known to undergo a reversible pressureinduced phase transformation at~0.8 GPa to e-eucryptite. This study correlates the results between two techniques, in situ diamond anvil cell-Raman spectroscopy and nanoindentation experiments, to explore how doping (substituting Zn for Li) influences this pressure-induced phase transformation. Diamond anvil cell tests carried up to 3 GPa hydrostatic stress under Raman spectroscopy were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In their recent high-pressure X-ray diffraction (XRD) experiments, Zhang amorphize at pressures of 3-5 GPa via reconstructive transformations with significant changes in atomic coordinations, 18,41 and suggested that PIA in b-eucryptite is possibly assisted by mechanical instability and kinetic hindrance of equilibrium phase transformations owing to reduced atomic mobility at 300 K. 18 Furthermore, recent nano-indentation studies have revealed that the pressure-induced transition in b-eucryptite is associated with an activation volume similar to that of SiO 4 and AlO 4 tetrahedra. 42,43 However, the atomic-scale mechanisms that govern PIA in b-eucryptite and the detailed structural characteristics of the amorphous phase are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In their recent high-pressure X-ray diffraction (XRD) experiments, Zhang amorphize at pressures of 3-5 GPa via reconstructive transformations with significant changes in atomic coordinations, 18,41 and suggested that PIA in b-eucryptite is possibly assisted by mechanical instability and kinetic hindrance of equilibrium phase transformations owing to reduced atomic mobility at 300 K. 18 Furthermore, recent nano-indentation studies have revealed that the pressure-induced transition in b-eucryptite is associated with an activation volume similar to that of SiO 4 and AlO 4 tetrahedra. 42,43 However, the atomic-scale mechanisms that govern PIA in b-eucryptite and the detailed structural characteristics of the amorphous phase are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…13,[16][17][18][19] In addition, βeucryptite (a LiAlSiO 4 polymorph) exhibits a pressureinduced phase transformation at pressures that are low enough to be exploited technologically. 20,21 The crystal structure of β-eucryptite (space group P6 4 22 or P6 2 22) can be described as a stuffed derivative of β-quartz. 10,[12][13][14] For this structure, Morosin et al 15 reported a phase transformation occurring at pressures as low as ∼ 0.8GPa.…”
mentioning
confidence: 99%